Methane oxidation in landfill cover soil; the combined effects of moisture content, nutrient addition, and cover thickness. Issue 2 (1st March 2007) - Warith, Mostafa; Fernandes, Leta; Albanna, Muna
Abstract : Oxidation of methane by methanotrophs in the landfill cover soil provides a source reduction for methane. Full factorial 2 3 experimental design using heterogeneous batch reactors was conducted to investigate statistically the individual and combined effects of soil moisture content, nutrient addition, and cover thickness on the CH4 oxidation process, during the migration through a landfill cover soil. Adding fertilizer as nutrient source to the 200 mm layer thickness of the landfill cover soil that contained 30% moisture content increased the CH4 oxidation efficiency from 38% to 81%. While, adding nutrients to the soil with less moisture content (15%) affected negatively the bacterial performance of methane oxidation, possibly as a result of toxicity or microbial water stress. Kinetic constants were reported and statistical design model was developed to describe the expected methane oxidation efficiencies under different levels of moisture content and nutrient addition that occur in a typical landfill cover soil.